The effect of gymnastics training on anthropometric, somatotype and some performance characteristics in preschool girls - Genc, Harun; Cigerci, Ali Erdem (Progress in Nutrition, 2020)
Purpose: The purpose of this study was to examine the effects of gymnastics training on somephysical and performance characteristics in 6-7 age group pre-school girls. Method: In the study, height, bodyweight (BW), BMI (body mass index), BFP (body fat percentage), skinfold thickness (SFT), diameter measurement (DM), circumference measurement (CM), sitting height (SH), arm span (AS) and also for performance measurements vertical jump (VJ), standing long jump (SLJ) and flexibility tests were used as pre-test and post-test to the experimental group (EG) and control group (CG). The analysis of the data was evaluated in the SPSS 22 package program. The analyses related to inter-group, intra-group and the effect of training were made by multiple measures analysis of variance (MANOVA) in repeated measurements. Post Hoc comparisons in significant values were determined by Bonferroni Test. The significance level was accepted as 0,05. Findings: After 12 weeks of gymnastics training, it was seen statistically increase in height, SH and ASin favor of EG, statistically decrease in BFP value in EG, statistically increase in BW value in both groups, statisticallyincrease in BMI value in CG. In addition, when the pre-test and post-test measurement results of the groupswere examined, no significance in performance characteristics was found in CG, there was also statisticallysignificant difference in all performance characteristics in EG. Result: It can be said that 12-week gymnasticstraining has a positive effect in terms of height, SH, AS, VJ, SLJ and flexibility in 6-7 age group girls.